A case report of prostate cancer with leptomeningeal metastasis. Issue 8 (5th June 2021) - Dehghani, Mansoureh; PeyroShabany, Babak; Shahraini, Ramin; Fazilat‐Panah, Danial; Hashemi, Fateme; Welsh, James S.; Javadinia, Seyed Alireza
Abstract: Background: Prostate cancer is the most prevalent cancer in men. However, leptomeningeal involvement by prostate carcinoma is a rare event. Case: Here, we report a 69‐year‐old patient with castration‐resistant metastatic prostate cancer who presented with headache and ataxia. Brain MRI revealed a huge invasive interaxial mass at right occipital lobe with diffuse thickening and enhancement of meninges, the arachnoid, and the pia mater, and he was diagnosed with leptomeningeal carcinomatosis. The patient received whole brain radiotherapy. Conclusion: Despite the fact that brain and leptomeningeal metastases are not very common in patients with prostate cancer, signs and symptoms of nervous system disorders should be assessed carefully, and consideration of such unusual metastases must be considered.